Investigating teachers’ perceptions on unemployment caused by the possibility of deploying robots into the teaching profession: a case of three schools in South Africa - Sitoe, Maida Carlos (University of the Witwatersrand, Johannesburg, 2024)
The influence of globalization is inevitable and the quest to remain globally relevant has created a growing demand for integrating technology into different facets of life in response to the Fourth Industrial Revolution (4IR). The challenge of introducing technology into various sectors of the economy shifts away from the demand for low-medium skilled candidates to a need for highly skilled candidates which in turn would lead to automation and mass unemployment. Teaching is considered one of the most secure jobs in the world. However, the introduction of social robots in classrooms to serve as teachers or assistants may be seen as a threat to teacher employment. One of the repercussions of introducing Robot teachers into classrooms despite raising concerns regarding practicality and learner’s safety, further intensifies teacher insecurities regarding the teaching profession. Despite the substantial amount of literature addressing the concept of robots about teaching and how teachers perceive the concept of robots replacing their role; most existing literature focuses on how deploying robots can enhance teaching and learning. It addresses the practicality of deploying robots and raises awareness of ethical concerns regarding learner’s safety. Thus, to the researcher’s knowledge, there are hardly a limited number of studies that address how teachers feel about the concept of robot teachers replacing them in a South African context. As a result, this study aimed to investigate the different teacher perceptions on the possibility of deploying robots in South Africa. The study was quantitative and utilized a positivist approach. Data was collected from three different South African schools classified as Quintile 1, Quintile 4, and Quintile 5, through a closed-ended survey questionnaire and interviews. The sample consisted of 45 secondary school teachers serving as post levels 1 and for further analysis only 4 teachers were selected for a face- to-face interview. Findings show that most teachers do not fear the notion of being replaced by robots. Due to limitations such as Economic constraints, poor infrastructure lack of resources, inequalities and lack of access, 73% of the teachers believe that integrating robot teachers in a vi | P a g e South African context is impractical. Surprisingly, 80% of teachers feel and believe that robots should only be employed to assist teachers in performing daily tasks in a classroom
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Robot teacher; Unemployment; Education technology; SDG-4: Quality education; SDG-9: Industry, innovation and infrastructure